AI-Based Design of Robust PSS Guided by D-Decomposition - Fathy, M.; Keshta, H. E.; Ali, Mahmoud N.; Soliman, M. (Power System Conference, MEPCON, International Middle-East, 2024)
This paper aims to design an effective Power System Stabilizer (PSS) to enhance the rotor angle stability of a Single Machine Infinite Bus bar system (SMIB) using a D-Decomposition approach. Also, the system robustness under uncertainties is investigated in this paper. An advanced optimization algorithm, called Manta-ray Foraging Optimization (MRFO), is proposed to compute the optimum parameters of lead-lag compensator based PSS considering the system nonlinearities. The proposed design based on MRFO algorithm is compared to the design optimized using another meta-heuristic algorithm to emphasize the superiority of the proposed algorithm using Integral Time Absolute Error (ITAE) as a performance index. Robustness test based on Hermite-Biehler theorem showed that system is stable subject to parametric uncertainties.